Visualisation of female characters in Huturu Hwemavanga (Vernom from the Scars), Chakwesha (The Boss) and Nguva Yakaoma (Hard Times) - Charles Tembo; llan T Maganga (Taylor & Francis Online., 2023)
This paper is a comparative exegesis of Zimbabwean novelists’ visualisation of female characters. It avers that in addressing business management issues through literature, selected Shona novelists’ projection of female characters fosters hopelessness and despair into the unsuspecting readership since works of art is never neutral but rather ideological. Utilising Chakwesha (The Boss), Huturu Hwemavanga (Vernom from the Scars) and Nguva Yakaoma (Hard Times) as the prisms for the study, this paper holds that in business management and administration issues; women are cast as tricksters, opportunists, fraudsters and responsible for businessmen’s downfall in their pursuit of business triumphalism. In all the selected primary sources for this paper, women are the perpetrators, whereas their male counterparts are the victims. Furthermore, the paper argues that this illumination fosters pessimism instead of a life-affirming and life-guaranteeing consciousness in the audience through the manner these Shona novelists pit male and female characters against each other. Since literature helps shape people’s attitudes and identity, novelists have to elucidate on the predatory nature of the capitalistic economic system, which undergirds a neo-colonial system, which in turn impacts on respective female characters’ morality that these novelists tend to magnify. Appreciation of these selected African literary works is guided by Africana Womanism against the backdrop that it places cultural and historical circumstances in the explication of issues related to the condition of African women.